Three Fragments of Empedocles of Acragas An Interpretation through the Lens of Cultural Myth Criticism - Calabrese, Claudio; Junco, Ethel Beatriz (Amaltea. Revista de Mitocrítica, 2026)
This article explores three fragments of Empedocles through cultural myth criticism, focusing on the relationship between myth, cosmology, and soteriology. Set within the transition from Archaic to Classical Greece, it examines the concepts of philótēs and neîkos to elucidate the cosmic cycle and the soul’s purification. Through philological and comparative analysis with Orphic and Pythagorean traditions, the study argues that Empedoclean poetry unites natural knowledge and religious experience, creating a hierophanic language that fuses myth and philosophy. In doing so, it reactivates a primordial time where archetypal truths emerge, offering a unified vision of the cosmos and human destiny.